Facade, Kaisar-i-Hind building - Ghosh, Ayan (2023)
Kaisar-i-Hind is located on Currimbhoy Road, named after Ebrahim Currimbhoy (1839-1924), a Gujarati Khoja businessman who founded E. Pabaney & Co. and made a fortune in the opium trade with China. He was nominated Trustee of the Port of Bombay. For his services, the British conferred E. Currimbhoy with Knighthood (1905) and Baronetcy (1910).